2016
DOI: 10.1080/02770903.2016.1180697
|View full text |Cite
|
Sign up to set email alerts
|

A regional cohort study of the treatment of critically ill children with bronchiolitis

Abstract: Even within a close geographic region, there is significant variation in the treatment provided to critically ill children with RSV bronchiolitis. None of these treatments were associated with shorter durations of hospitalization in this population and some, such as mechanical ventilation, were associated with longer ICU lengths of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 27 publications
1
16
0
4
Order By: Relevance
“…Although there were minor annual fluctuations during the study period, the overall rate of detection of adenovirus, hMPV and other IQR (interquartile range), *median of days, † for patients who was endotracheally intubated. respiratory viruses was not as high as compared to published studies of non-PICU settings (7,(19)(20)(21)(22). The potential reasons could be related to our inclusion criteria, i.e.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although there were minor annual fluctuations during the study period, the overall rate of detection of adenovirus, hMPV and other IQR (interquartile range), *median of days, † for patients who was endotracheally intubated. respiratory viruses was not as high as compared to published studies of non-PICU settings (7,(19)(20)(21)(22). The potential reasons could be related to our inclusion criteria, i.e.…”
Section: Discussionmentioning
confidence: 74%
“…The hospital outcomes in the eight viruses were addressed in Table 2. Among all the viruses, adenovirus had a clinically significantly higher endotracheal intubation rate (36/50, 72%) and longer hospital LOS (19 days, IQR: [11][12][13][14][15][16][17][18][19].…”
Section: Patients' Demographicsmentioning
confidence: 99%
“…Numerous studies have shown wide variation in the therapeutic management of moderate AB [7, 8]. Despite a lack of evidence, personal or institutional preferences are often maintained when AB patients require admission to the PICU [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…There is significant heterogeneity in the routine care of infants with bronchiolitis among clinicians (11)(12)(13)(14). The use of furosemide in the management of bronchiolitis is not uncommon, though it is unproven.…”
Section: Discussionmentioning
confidence: 99%